2023
DOI: 10.1186/s13059-023-02874-4
|View full text |Cite
|
Sign up to set email alerts
|

The genetic and evolutionary basis of gene expression variation in East Africans

Abstract: Background Mapping of quantitative trait loci (QTL) associated with molecular phenotypes is a powerful approach for identifying the genes and molecular mechanisms underlying human traits and diseases, though most studies have focused on individuals of European descent. While important progress has been made to study a greater diversity of human populations, many groups remain unstudied, particularly among indigenous populations within Africa. To better understand the genetics of gene regulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…In spite of our limited sample size, these findings suggest a distinctive and distinguishable (relative to previously characterized European data) Indonesian sQTL signal, as we would expect sharing between GTEx and BLUEPRINT to also be negatively impacted by the relatively low sample size in BLUEPRINT and their distinct processing pipelines. By profiling the differences and similarities across these groups, we can more accurately characterize the gene regulatory mechanisms underlying diversity in genetic traits, highlighting the value of trans-ethnic, trans-environment QTL mapping to maximize discovery of gene regulatory variation across humans [30, 32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of our limited sample size, these findings suggest a distinctive and distinguishable (relative to previously characterized European data) Indonesian sQTL signal, as we would expect sharing between GTEx and BLUEPRINT to also be negatively impacted by the relatively low sample size in BLUEPRINT and their distinct processing pipelines. By profiling the differences and similarities across these groups, we can more accurately characterize the gene regulatory mechanisms underlying diversity in genetic traits, highlighting the value of trans-ethnic, trans-environment QTL mapping to maximize discovery of gene regulatory variation across humans [30, 32].…”
Section: Resultsmentioning
confidence: 99%
“…A study of the response to infection in monocytes from individuals of European and African descent living in Belgium showed that genetic ancestry consistently contributed to differences in splicing, and highlighted the role of archaic introgression from Neanderthals [21] in particular. Recently, a separate study examining both expression and splicing in whole blood in East African populations has shown that overall, the genetic architecture of splicing is shared between individuals of African and European ancestry, but nonetheless identified a substantial number of sQTLs in individuals from Tanzania and Ethiopia that have not been reported in European cohorts [32].…”
Section: Introductionmentioning
confidence: 99%
“…76 While researchers have identified over 150 genes associated with human skin pigmentation, the relationship between population-specific selective pressure and the expression of skin pigmentation-associated genes is only marginally understood. 77 Genetic data from ancient Europeans outlines the complexity in the spread of pigmentation alleles, mapping the timing of migration events with cultural shifts both shaping the demography of early Europeans. Still, the complex history of skin pigmentation is less well understood outside of a European context.…”
Section: Discussionmentioning
confidence: 99%
“…Data from public health studies have contextualized the biological significance of vitamin D, underscoring the advantages of sufficient cutaneous vitamin D synthesis 76 . While researchers have identified over 150 genes associated with human skin pigmentation, the relationship between population‐specific selective pressure and the expression of skin pigmentation‐associated genes is only marginally understood 77 . Genetic data from ancient Europeans outlines the complexity in the spread of pigmentation alleles, mapping the timing of migration events with cultural shifts both shaping the demography of early Europeans.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, these resources have been limited [7][8][9][10] . Given the increased genomic diversity and lower linkage disequilibrium 11,12 in African populations relative to other global populations, functional genomic studies provide increased opportunity to map functional elements, identify functional variants, and understand their roles in complex traits and disease [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%